Applications of power ultrasound in oriented modification and degradation of pectin: A review. (October 2018) - Wang, Wenjun; Chen, Weijun; Zou, Mingming; Lv, Ruiling; Wang, Danli; Hou, Furong; Feng, Hao; Ma, Xiaobin; Zhong, Jianjun; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: Recently modified pectin (MP) showed improved functional properties and bioactivities than the native one. Ultrasound, as one of the green technologies, was investigated to degrade and modify bioploymers with high efficiency and low cost. In an aqueous system with pectin, ultrasonication creates localized high temperature and pressure spots, and produces "microjets" and free radicals, which contribute to modify the structural, functional, and bioactive properties of pectin. The factors influencing pectin modification include ultrasound frequency, power intensity, temperature, treatment time and duty cycle. Precise control of these parameters is critical for ultrasound technology to produce products with consistent and predictable properties. This work summarizes recent advances in applications of power ultrasound technology in oriented degradation and modification of pectin. Different degradation processing situations and the degradation phenomena of pectin during extraction have been reviewed. Furthermore, future trends to better utilize this green technology have also been purposed. Highlights: Power ultrasound can degrade and modify structure and properties of pectin. Better properties and higher bioactivities of pectin can be attained by sonication. Ultrasonic extraction of pectin always accompanied by degradation. Trends in better developing ultrasound for pectin applications suggested.